PROSPEK DAN TANTANGAN USAHATANI TEMBAKAU MADURA - Fuad Hasan; Dwidjono Hadi Darwanto (Universitas Sebelas Maret, 2013)
Tobacco has an important role in the socio-economic life of the community, such as the State in the form of tax revenue and foreign exchange earnings,employment, the income of farmers, laborers, and merchants, as well as revenue. But on the other hand, under the pretext of health, development and trading of tobacco began to get legalized opposition through regulations. This has an impact on the survival of tobacco farming, which in turn have an impact on the welfare of farmers. This paper aims to discuss the prospects and challenges facing tobacco farmers inMadura. In addition, tobacco farmers face problems: marketing systems, productivity, and bargaining position. Alternative solutions are 1) reduction in acreage planted; 2) replacement of plants; 3) low nicotine tobacco cultivation; 4) diversification of derivative products; 5) optimization of the institutional.